Phylogenetic signal and major ecological shifts in the ecomorphological structure of stream fish in two river basins in Brazil - Roa-Fuentes, Camilo Andres [UNESP]; Casatti, Lilian [UNESP]; Romero, Renato de Mei (Soc Brasileira Ictiologia, 2015)
We tested the contribution of the phylogenetic and specific components to the ecomorphological structure of stream fish from the upper Paraguai River and upper Sao Francisco River basins, and identified nodes in the phylogenetic tree at which major ecological shifts occurred. Fish were sampled between June and October of 2008 in 12 streams (six in each basin). In total, 22 species from the upper Paraguai River basin and 12 from the upper Sao Francisco River were analyzed. The ecomorphological patterns exhibited phylogenetic signal, indicating that the ecomorphological similarity among species is associated with the degree of relatedness. A strong habitat template is most likely to be the primary cause for a high phylogenetic signal. A significant contribution from the specific component was also detected, supporting the idea that the phylogenetic signal occurs in some clades for some traits, but not in others. The major ecological shifts were observed in the basal nodes, suggesting that ecological niche differences appear to accumulate early in the evolutionary history of major clades. This finding reinforces the role of key traits in the diversification of Neotropical fishes. Ecological shifts in recent groups could be related to morphological modifications associated with habitat use.
Keywords: Morphological diversity; Niche conservatism; Ecophylogenetics; Paraguay basin; Sao Francisco basin